Finite element formulations applied to outer ear modeling - Volandri, Gaia (Strojniški vestnik, 2014)
The work described in this paper is part of a broader research activity on the development of a virtual ear. The present study focuses on the tympanic membrane and auditory canal modeling, which are important components in sound transmission. The standard finite element method (FEM) and an alternative method (the generalized FEM), suitable for modeling sound propagation at high frequencies, were applied. Two domains (fluid and structural) for the auditory canal and the tympanic membrane, respectively, were considered in order to evaluate the coupling of the different methods and to apply a fluid-structure interaction formulation. ANSYS software was used for solving FEM analyses, while GFEM simulations were obtained by implementing the method in Wolfram Mathematica. Simulation results include modal response, pressure distribution in the auditory canal and displacement distribution in the tympanic membrane. The identified modal frequencies of the auditory canal agree with published data reported in the literature. The validation of such method with standard FEM simulation at increasing mesh density shows that FEM is more suitable for simulations of the human ear in the audible frequency range, although the generalized formulation could be convenient if an ear model including the whole head or the ultrasound frequency range were investigated.
Keywords: finite element method; metoda končnih elementov; prenos zvoka; simulacije; sluhovodi